Introduction to psycholinguistics : understanding language science - Traxler, Matthew J. (Wiley-Blackwell, 2012)
"This textbook offers a cutting edge introduction to psycholinguistics, exploring the cognitive processes underlying language acquisition and use. Provides a step-by-step tour through language acquisition, production, and comprehension, from the word level to sentences and dialogue Incorporates both theory and data, including in-depth descriptions of the experimental evidence behind theories Incorporates a comprehensive review of research in bilingual language processing, sign language, reading, and the neurological basis of language production and comprehension Approaches the subject from a range of perspectives, including psychology, linguistics, philosophy, computer science, neurology, and neurophysiology Includes a full program of resources for instructors and students, including review exercises, a test bank, and lecture slides, available upon publication at www.wiley.com/go/traxler "--